Two types of cleavage, from zygote to three cells, result in different clinical outcomes and should be treated differently - Nemerovsky, Luba; Ghetler, Yehudith; Wiser, Amir; Levi, Mattan (Frontiers in Cell and Developmental Biology, 2024)
Research Question: What is the utilization rate of embryos which exert inadequate zygote cleavage into 3 daughter cells.Design: This study used a retrospective dataset from a single IVF Unit. A total of 3060 embryos from 1811 fresh IVF cycles were analyzed. The cleavage pattern, morphokinetics, and outcome were recorded. Only 2pn embryos, fertilized by ejaculated sperm, cultured in time-lapse system for at least 5 days were included.We generated three study groups according to embryo's cleavage pattern: (I) Control, normal cleavage (n=551); (II) fast cleavage, zygote to three cells within 5 hours (n=1587); (III) instant direct tripolar cleavage from zygote to three cells (n=922).The rate of usable fast cleavage blastocysts was 108/1587 (6.81%) and usable control blastocysts 180/551 (32.67%). The time of PN fading and from fading to first cleavage, differed significantly between the three groups. Although the pregnancy rate of control and fast cleavage blastocysts were comparable (40.35% and 42.55%, respectively), the amount of instant direct cleavage embryos that reached blastocyst stage was neglectable (only 4 embryos out of 922 analyzed IDC embryos) and unsuitable for statistical comparison of pregnancy rates.Our results indicate the need to culture instant direct cleavage embryos for 5 days, up to the blastocyst stage, avoiding transfer of embryos that are fated to arrest even when their morphological grade on day 3 is acceptable, whereas fast cleavage embryos could be transferred on day 3 when there is no alternative.